AXIOLOGICAL VIEW OF CHEMO-ENTREPRENEURSHIP IN SUPPORTING THE PANCASILA STUDENT PROFILE - Agus Kamaludin; Nahadi; Sjaeful Anwar (Jurnal Cakrawala Ilmiah, 2023)
High unemployment of secondary school graduates is a significant challenge the Indonesian government faces. One solution that can be done to overcome this problem is through learning chemistry with an entrepreneurial approach (Chemo-Entrepreneurship). The chemo-entrepreneurship approach supports achieving the Pancasila student profile in the independent curriculum. The analysis focuses on an axiological view of chemistry learning with a chemo-entrepreneurship approach in high school regarding ethical and aesthetic values. This research is qualitative research using a literature study or literature review method. Data collection techniques were carried out by collecting some literature from books, the internet, and related journal articles. The chemo-entrepreneurship approach makes the chemistry students learn valuable through making a product. Products can be designed so that they have selling power. These skills are handy for graduates entering society to create jobs, thereby reducing the unemployed. Learning projects with a Chemo-entrepreneurship approach support the achievement of Pencasila student profiles.